Outcomes From a Randomized Trial of a Bilingual mHealth Social Media Intervention to Increase Care Engagement Among Young Gay, Bisexual, and Other Men Who Have Sex With Men and Transgender Women With HIV. (December 2022) - Rhodes, Scott D.; Tanner, Amanda E.; Mann-Jackson, Lilli; Alonzo, Jorge; Song, Eunyoung Y.; Smart, Benjamin D.; Garcia, Manuel; McCoy, Thomas P.; Schafer, Katherine R.; Wilkin, Aimee M.
Background: The North Carolina Community Research Partnership developed, implemented, and tested weCare, a 12-month bilingual mHealth social media intervention designed to reduce missed HIV care appointments and increase viral suppression among racially/ethnically diverse gay, bisexual, and other men who have sex with men (GBMSM) and transgender women living with HIV by harnessing established social media platforms (i.e., Facebook, texting, and dating apps). Methods: We randomized 198 GBMSM and transgender women (mean age = 26) living with HIV to the weCare intervention ( n = 100) or usual-care ( n = 98) group. Inclusion criteria included being newly diagnosed or not in care. Participants completed structured assessments at baseline and 6-month postintervention follow-up (18 months after baseline data collection). HIV care appointment and viral load data were abstracted from each participant's electronic health record at baseline and follow-up. Follow-up retention was 85.5%. Results: Among participants, 94% self-identified as cisgender men, 6% as transgender, 64% as African American/Black, and 13% as Latine. Participants in both groups significantly reduced missed HIV care appointments and increased viral suppression at follow-up compared with baseline. However, there were no significant differences between weCare and usual-care participants for either outcome at follow-up. Conclusions: An intervention effect was not identified for our two primary outcomes. Several factors may have influenced the lack of significant differences between weCare and usual-care participants at follow-up, including intervention implementation (e.g., staffing changes and lack of fidelity to the intervention as originally designed by the partnership), data collection (e.g., data collection time points and retention strategies), and clinical (e.g., contamination) factors.